Direct and averted gaze modulate the event-related brain responses to social exclusion signals - Yu-Fang Yang; Xu Fang; Michael Niedeggen (Scientific Reports)
Abstract Social exclusion is a negative experience in social interaction which can be modulated by the perceived eye gaze. In our Cyberball study, we asked how gaze direction – direct versus averted – affects the processing of social exclusion by using electroencephalogram (EEG) methods. Participants encountered neutral gazes in the inclusion phase (Block1) and then either direct or averted gazes during the exclusion phase (Block2). We measured self-reports on Need-Threat Questionnaires (belonging, control, meaningful existence, self-esteem) and negative mood, along with event-related potentials (ERPs), specifically the P3 component (P300) - an indicator of expectation violation. Findings demonstrated that the P3 amplitude showed differential changes between gaze conditions during the transition from inclusion to exclusion, with direct gaze eliciting stronger neural responses. This difference signals that direct gaze enhances the expected participation, thus sensitizing participants for exclusionary signals. Simultaneously, self-reports indicated that the transition evoked weaker negative emotions in the direct gaze group and stronger negative emotions in the averted gaze group, signalling that direct gaze also serves as an affiliative signal. These results illuminate how gaze directions shape cognitive and emotional reactions to social exclusion. However, further research is necessary to unravel these effects amidst other non-verbal cues and fully comprehend their impact on neural and behavioural responses to social exclusion.